2015
DOI: 10.1080/02640414.2015.1026374
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic, kinetic and EMG analysis of four front crawl flip turn techniques

Abstract: This study aimed to analyse the kinematic, kinetic and electromyographic characteristics of four front crawl flip turn technique variants. The variants distinguished from each other by differences in body position (i.e., dorsal, lateral, ventral) during rolling, wall support, pushing and gliding phases. Seventeen highly trained swimmers (17.9 ± 3.2 years old) participated in interventional sessions and performed three trials of each variant, being monitored with a 3-D video system, a force platform and an elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 14 publications
1
34
0
1
Order By: Relevance
“…Overall, researchers had a strong interest on the swim stroke, disregarding the acyclic phases of the race (i.e., the start and the turn). Albeit, studies can be found about such topic (e.g., Pereira et al, 2015;Vantorre, Seifert, Fernandes, Vilas-Boas, & Chollet, 2010;Veiga, Roig, & Gómez-Ruano, 2016). However, there is no evidence about how elite swimmers behave in major competitions in all four strokes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, researchers had a strong interest on the swim stroke, disregarding the acyclic phases of the race (i.e., the start and the turn). Albeit, studies can be found about such topic (e.g., Pereira et al, 2015;Vantorre, Seifert, Fernandes, Vilas-Boas, & Chollet, 2010;Veiga, Roig, & Gómez-Ruano, 2016). However, there is no evidence about how elite swimmers behave in major competitions in all four strokes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was reported that the start performance should rely on the optimisation of the underwater phase (i.e., gliding, dolphin kicks and water breakout) before starting the swim stroke (e.g., Guimarães & Hay, 1985). The body of knowledge on turning is also rather scarce, when comparing to the swim stroke (e.g., Pereira et al, 2015;Slawson, Conway, Jusham, Le Sage, & West, 2010;. A study conducted by Mason and Cossor (2001) concluded that the fastest swimmers were not the fastest turners.…”
Section: Introductionmentioning
confidence: 99%
“…Two start block projects were previously designed: (i) a bulky and solid structure and (ii) a lattice block with a declination support, which was replaced by a lattice galvanized steel structure with zero inclination due to excessive mass and reduced stability showed by the previous structures. The starting block was projected to be fixed over an underwater structure attached vertically to the swimming pool wall by front and rear edges, being similar to a previous structure used by Pereira et al [13,14] and de Jesus et al [24] for flip turn and backstroke start kinetics assessment. The first underwater structure included a two independent force plates support.…”
Section: Start Block Underwater Structure Handgrips and Feet Supportmentioning
confidence: 99%
“…The description of forces generated during swimming turns also started in the 1970s using uniaxial force plates to assess the horizontal component in tumble and open turns (e.g., [11]). Swimming turns external forces analysis using three-dimensional force plates is still scarce, with the flip technique and its variants being the most commonly investigated (e.g., [12,13]). A double underwater tri-axial force plate solution developed for independent assessment of forces applied by each foot in a backstroke start can also provide a direct measurement of the combined forces exerted during turns and the determination of foot position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation